The Effect of High-Intensity Circuit Training versus Low-Intensity Interval Training on Functional Strength and Weight Efficacy in Overweight and Obese Young Females- A Randomized Clinical Trial - Huma Nayyab; Sarah Ehsan; Farwah Batool; Wajeeha Mahmood; Tahir Mahmood (Journal of the Dow University of Health Sciences, 2023)
Objective: To compare the effects of high-intensity circuit training (HICT) versus low-intensity interval training (LIIT) on functional strength and weight efficacy in overweight and obese young females. Methods: This randomized clinical trial was conducted at Ladies Club Gujranwala Cant, Pakistan from March 2021 to January 2022. Participants, aged 18-35, were randomly assigned to HICT or LIIT groups. Functional strength and weight efficacy were taken as outcomes and measured at baseline and the 8th week after the interventions. Leg levers, modified push-ups, squats, cordless skipping, and burpees were used to test functional strength. The Weight Efficacy Lifestyle Questionnaire Short Form (WELQS) was used to measure weight efficacy. Results: Of total 34 young females (17 in HICT and 17 in LIIT group), the median waist circumference was found significantly higher in the HICT group as compared to the LIIT group i.e., 39.0 (37.0 – 42.5) inches vs. 36.0 (33.0 – 38.5) inches (p-value 0.046) respectively. Similarly, the median hip measurement of the females was found significantly higher in the HICT group 45.0 (40.5 – 48.0) inches as compared to the LIIT group 41.0 (39.0 – 44.5) inches (p-value 0.029). Within-group comparison at baseline and after 8 weeks showed a significant median difference, with pushups, leg levers, burpees, left leg squats, right leg squat, skipping, and weight efficacy (p-value <0.001) respectively. Conclusion: This study concludes that both HICT and LIIT improved functional strength and weight efficacy in overweight and obese young females.